Three isolates among 138 sponge-associated bacteria were isolated from Waigeo Island, Raja Ampat West Papua Province, Indonesia, have been shown protease inhibitory activity against subtilisin (serine protease), thermolysin (metalloprotease), and crude extract from pathogenic bacteria (Eschericia coli enteropathogenic/EPEC K.1.1, Staphylococcus aureus, and Pseudomonas aeruginosa). Those three isolates were designated as sponge associated bacteria SAB S-12, SAB S-21, and SAB S-17. A simple casein - ARIS TRI WAHYUDI; . QATRUNNADA; NISA RACHMANIA MUBARIK (HAYATI Journal of Biosciences, 2010)
Three isolates among 138 sponge-associated bacteria were isolated from Waigeo Island, Raja Ampat West Papua Province, Indonesia, have been shown protease inhibitory activity against subtilisin (serine protease), thermolysin (metalloprotease), and crude extract from pathogenic bacteria (Eschericia coli enteropathogenic/EPEC K.1.1, Staphylococcus aureus, and Pseudomonas aeruginosa). Those three isolates were designated as sponge associated bacteria SAB S-12, SAB S-21, and SAB S-17. A simple casein and Sea Water Complete (SWC) double layer agar method was used to screen the bacteria against pathogenic bacteria producing protease, i.e. EPEC K.1.1, S. aureus, and P. aeruginosa. Among them, SAB S-12 isolate showed no inhibitory zone indicated. The isolate had the highest inhibitory activity against subtilisin and crude extract enzyme of pathogenic bacteria, the inhibitory activity was 91.6 and 98.9%, respectively. In addition, the SAB S-21 isolate had the highest inhibitory activity against thermolysin, it was 70.4%. The optimum pH and temperature for protease inhibition of the three isolates was at pH 7.0-8.0 and 40-50 oC respectively. Based on 16S rRNA gene sequence, the closest related with SAB S-12, SAB-17, and SAB-21 isolates was Providencia sp. (92% identity), Paracoccus sp. (86% identity), and Bacillus sp. (% identity), respectively.